A critical review of clinical trials in systemic lupus erythematosus. (September 2016) - Mahieu, M A; Strand, V; Simon, L S; Lipsky, P E; Ramsey-Goldman, R
One challenge in caring for patients with systemic lupus erythematosus (SLE) is a paucity of approved therapeutics for treatment of the diverse disease manifestations. In the last 60 years, only one drug, belimumab, has been approved for SLE treatment. Critical evaluation of investigator initiated and pharma-sponsored randomized controlled trials (RCTs) highlights barriers to successful drug development in SLE, including disease heterogeneity, inadequate trial size or duration, insufficient dose finding before initiation of large trials, handling of background medications, and choice of primary endpoint. Herein we examine lessons learned from landmark SLE RCTs and subsequent advances in trial design, as well as discuss efforts to address limitations in current SLE outcome measures that will improve detection of true therapeutic responses in future RCTs.